MESS to live with schizophrenic parental history: A systematic review of developmental checkpoints. - Maryam Khan; Rabia Batool; Uzma Mushtaq; Shakir Iqbal; Sana Shaheen; Aimen Zafar Butt; Anees Ahmed (PLoS ONE)
Parental history of schizophrenia, a complex and multifaceted psychological disorder, is recognized as a well-established risk factor in the development of the disorder among offspring. However, the developmental patterns of such children and adolescents before the onset of the problem have not yet been systematically documented. We present a comprehensive account of developmental checkpoints essential for preventing it from occurring. This review embarks on a detailed explanation of the domains requiring serious attention during the development of an individual with such a familial history. We examined a diversified set of studies comparing the developmental patterns of children with or without (a comparative) a parental history of schizophrenia and highlighted the areas of concern for the later development of the problem among the first group. We included the peer-reviewed articles, published in English based on children and adolescents, found in Web of Science, PubMed, and PsychInfo databases and separate citation searches. We summarized our findings under MESS typology covering motor development, emotional and behavioral issues, speech and hearing impairments, and socio-cognitive aspects as essential features of a child's development serving as a guide to prevent the onset of psychological complications.